PRARANCANGAN PABRIK MALEIC ANHYDRIDE DARI BUTANA Kapasitas 20.000 Ton/Tahun - , IRSAN IBADURRAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Maleic anhydride is made by oxidation reaction between butane and air with presence of Vanadium Phosphor Oxyde (VPO) as catalyst in fixed bed mullti tube reactor. The plant was designed to operate on capacity of 20.000 tonnes/year, butane needs as much as 3.350.02 kg / hour and air needs as much as 113.463 kg / hour. Utilities needs include water as much as 32.279 kg / hour, electricity as much as 2.2 MVA , fuel oil as much as 1.230 kg / hour and compressed air as much as 100 m3/hour (STP). The planned factory was established in 2016 in the industrial area Cilegon, Banten. Land used as many as 5 hectares including residential and plant expansion. Plant work continuously for 24 hours per day for 330 days per year with 220 employers. Fixed Capital (FC) requirement of US$ 26,992,179.25 + Rp 107.139.930.359 and Working Capital (WC) of US$ 16,847,110.35 + Rp 28.013.666.995. Profit before tax of Rp 108.037.665.342 and after tax of Rp 54.018.832.671. Return On Investment (ROI) before tax is 28,65% and after tax is14,33%. Pay Out Time (POT) before tax is 2,59 years and after tax is 4,11 years. Break Even Point (BEP) is 47,97% from maximum production capacity whereas Shut Down Point (SDP) is 26,17%. With consideration of the characteristic of the raw materials and products, operating conditions, the consumers who need, and similar plants that already established in the world, so that this plant is classified as low risk plant. Restriction that applies is the value of BEP is 40-60% for plants in Indonesia, minimum ROI of 11%, five years maximum POT, and Discounted Cash Flow Rate of Return (DCFRR) which is 1,5 times higher than bank interest rates. Based on the results of the economic analysis and constraints, it can be concluded that the maleic anhydride plant from butane with capacity of 20.000 tonnes per year is interesting to study further.